Treatment-seeking behaviour and social status of women with pelvic organ prolapse, 4th-degree obstetric tears, and obstetric fistula in western Uganda - Krause, Hannah G.; Natukunda, Harriet; Singasi, Isaac; Hicks, Sylvia S. W.; Goh, Judith T. W. (International urogynecology journal, 2014)
This study looks at a trilogy of women’s health issues including severe pelvic organ prolapse, unrepaired 4th degree obstetric tears and obstetric fistula, all of which can cause significant suffering in the lives of women and their families. Methods Women undergoing surgery for severe pelvic organ prolapse, unrepaired 4th degree obstetric tears and obstetric fistulae, were interviewed to assess their perceptions of what caused their condition, subsequent impact on their social situation and sexual activity, and whether they had sought treatment previously. Results One hundred fifty women participated in the survey, including 69 undergoing surgery for genito-urinary fistula, 25 with faecal incontinence only (including 24 women with unrepaired 4th degree obstetric tears and 1 woman with an isolated rectovaginal fistula), and 56 women with severe pelvic organ prolapse. All groups of women were exposed to abandonment by their families with 42 % of women with genito-urinary fistula, 21 % with unrepaired 4th degree obstetric tear, and 25 % of women with severe pelvic organ prolapse rejected by their husbands. Most of the women had actively sought treatment for their condition with no success due to unavailability of treatment or misinformation. Conclusions This study confirms the social stigma associated with obstetric fistula, however also highlights the social stigma faced by women suffering with severe pelvic organ prolapse and unrepaired 4th degree obstetric tears in western Uganda. There is an urgent need for education and training in obstetric management and pelvic organ prolapse management in such areas of limited resources.
Keywords: Social status; Obstetric fistula; Pelvic organ prolapse; Obstetric anal sphincter injury